2003
DOI: 10.1172/jci200317455
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of insulin and IGF-1 receptors on vascular endothelial cells protects against retinal neovascularization

Abstract: Both insulin and IGF-1 have been implicated in control of retinal endothelial cell growth, neovascularization, and diabetic retinopathy. To precisely define the role of insulin and IGF-1 signaling in endothelium in these processes, we have used the oxygen-induced retinopathy model to study mice with a vascular endothelial cell–specific knockout of the insulin receptor (VENIRKO) or IGF-1 receptor (VENIFARKO). Following relative hypoxia, VENIRKO mice show a 57% decrease in retinal neovascularization as compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 178 publications
(76 citation statements)
references
References 43 publications
6
68
0
2
Order By: Relevance
“…Inhibition of IGF-IR signaling has been shown to reduce VEGF production in tumor cells (36,37) and to interfere with retinal neovascularization through its effect on endothelial cells (38). Our data provide further support that these two pathways likely also interact in the SW527 tumor model.…”
Section: Induces Dynamic Changes Of Tumor Transcriptional Profilessupporting
confidence: 66%
“…Inhibition of IGF-IR signaling has been shown to reduce VEGF production in tumor cells (36,37) and to interfere with retinal neovascularization through its effect on endothelial cells (38). Our data provide further support that these two pathways likely also interact in the SW527 tumor model.…”
Section: Induces Dynamic Changes Of Tumor Transcriptional Profilessupporting
confidence: 66%
“…This is supported by our previous observation that mice with a vascular endothelial cell specific knock-out of the insulin receptor (VENIRKO) are protected from retinal neovascularization (7). Furthermore, in general, rates of development of retinopathy are somewhat lower in patients with insulin-resistant type 2 diabetes than in those with insulin-deficient type 1 diabetes (8,12).…”
supporting
confidence: 55%
“…Clinical studies have indicated that hyperglycemia and poor metabolic control are important factors in the development of diabetic retinopathy (1,2). Multiple mechanisms have been implicated, including relative hypoxia in retina, resulting in the induction of vascular endothelial growth factor (VEGF) 1 and other vascular mediators that stimulate proliferation of retinal endothelial cells in preretinal area (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Tissuespecific (Cre/lox) deletion of the IR in various tissues shows distinct phenotypes (17), including dyslipidemia in muscle (18), impaired glucose tolerance in adipose tissues (19), moderate insulin resistance and transient hyperglycemia in liver (20), impaired glucose tolerance in pancreatic ␤-cells (21), ␤-cell failure in brown adipocytes (22), obesity and reduced fertility in brain tissues (23), and protection against retinal neovascularization in vascular endothelial cells (24). The functional role of IRs in retina or photoreceptor cells is not known.…”
Section: Insulin Receptor (Ir)mentioning
confidence: 99%